2014
DOI: 10.5152/npa.2014.6999
|View full text |Cite
|
Sign up to set email alerts
|

Role of CRP, TNF-a, and IGF-1 in Delirium Pathophysiology

Abstract: Low IGF-1 levels can be used to predict delirium after surgery. However, the complex nature of cytokines and delirium itself make it difficult to utilize cytokines to predict delirium instead of psychometric tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The authors conclude that the direct relationship between the magnitude of non-infective inflammatory response and incidence of POCD has not been established. This is consistent with the data reported by Çinar et al that CRP, although elevated, cannot be considered as an independent risk factor in the development of POD [ 98 ]. On the other hand, a study, including the CRP levels performed by Kotfis et al, showed a correlation between increased CRP levels and delirium [ 62 ].…”
Section: Inflammation-related Biomarkerssupporting
confidence: 93%
See 2 more Smart Citations
“…The authors conclude that the direct relationship between the magnitude of non-infective inflammatory response and incidence of POCD has not been established. This is consistent with the data reported by Çinar et al that CRP, although elevated, cannot be considered as an independent risk factor in the development of POD [ 98 ]. On the other hand, a study, including the CRP levels performed by Kotfis et al, showed a correlation between increased CRP levels and delirium [ 62 ].…”
Section: Inflammation-related Biomarkerssupporting
confidence: 93%
“…Kazmierski et al showed an elevation of IL-2 and TNF-α levels in the postoperative period in coronary artery bypass graft (CABG) patients with delirium, and these results were independent of patient-related factors like age and gender, as well as their psychiatric and physical state and co-morbidities or perioperative factors like CPB time or duration of surgery [ 99 ]. According to Çinar et al, it is difficult to consider the postoperative value of TNF-α or CRP as an independent risk factor for POD [ 98 ]. However, Androsova et al mentioned that SIRS is the key factor, which may affect the brain and lead to neuroinflammation with IL-6 and TNF-α as biomarkers in predicting delirium [ 51 ].…”
Section: Inflammation-related Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five studies applied CAM to define POD [ 22 27 , 29 31 , 33 – 36 , 38 40 , 42 – 50 ] of which three were assessed with CAM and confirmed with the Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition, Text Revision; DSM-IV-TR) [ 25 27 ], and one was evaluated through CAM and the Delirium Rating Scale [ 24 ] (DRS: sensitivity of 82% and specificity of 94%, cut-off score of 10 [ 15 ]). Two studies used DRS to define delirium [ 21 , 28 ]. In one study, delirium was diagnosed using DSM-IV and DRS [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, relationship between direct measurement of TNF-alpha level and delirium has been controversial. In patients with delirium, multiple study reported that TNF-alpha remain not significant (De Rooij et al, 2007 ; Çinar et al, 2014 ; Brum et al, 2015 ). Of note, sample sizes of delirium cases in these reports are less than 100 (64 cases, 15 cases, and 17 cases, respectively), thus the result might have been underpowered.…”
Section: Discussionmentioning
confidence: 99%